REGIONAL DISPARITY IN PANGKEP REGENCY: A PERSPECTIVE ON INFRASTRUCTURE AVAILABILITY - Rahmi Rasjid (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2025)
Regional disparity with respect to infrastructure gaps is considered a benchmark for measuring inequality. In this study, the indicators for infrastructure availability are road infrastructure, education infrastructure, and health infrastructure. This policy paper aims to provide an overview of the phenomenon of inequality and its causes in Pangkajene and Islands Regency (Pangkep Regency) by examining the relationship between the infrastructure aspect and the reality of disparity in the region. It also aims to recommend policies related to infrastructure to reduce inequality in the regency. The method used to describe the inequality in Pangkep Regency is descriptive-quantitative, utilizing secondary data from the Central Statistics Agency (BPS) from 2021 to 2024 and sectoral data from Local Government Agencies. The study's findings reveal that the disparity in economic growth, as shown by the development of the Gini ratio index from 2021-2024, tends to be volatile and remains in the moderate category. The transportation infrastructure, specifically road length, has an effective contribution to reducing income inequality. The total road length in Pangkep Regency from 2021-2024 was 873.39 km. The aspect of education infrastructure also requires attention to prevent inequality in accessing educational services. Disparity in the health sector is also considered a contributor to inequality in Pangkep Regency, due to the uneven distribution of health infrastructure, particularly in areas with difficult accessibility, such as the islands. These findings are a strong message to the government to proportionally accelerate equitable development programs, especially in areas considered to be left behind, so that the infrastructure development process is not biased toward already developed areas